"Be ready, be steady, live happily": preventing falls due to medications' adverse effects / Dr. Mohd Shahezwan Abd. Wahab ... [et al.] - Abd. Wahab, Mohd Shahezwan; Zulkifli, Muhammad Harith; Ali, Aida Azlina; Ismail, Farhana Fakhira (Faculty of Pharmacy, 2023)
According to the Centers for Disease Control and Prevention (CDC), an older adult (age 65+) in the United States falls every second, making falls the leading cause of injury and injury-related death in this age group. According to recent Malaysian studies, falls among older people are a major concern, with one in every six older Malaysians falling at least once in a 12-month period. Falls are indeed dangerous and can have serious consequences, particularly among older people. They are the leading cause of external injuries and are responsible for 70% of all accidental deaths in people aged 75 and older. Hip fractures are a common injury caused by falls, and it is concerning that 25% of those who fracture their hips die within six months of the injury. Falls frequently necessitate hospitalisation, resulting in loss of independence, chronic pain, and decreased quality of life. Falls among older people are frequently attributed to a variety of risk factors, including medication use. Anticonvulsants, antidepressants, antipsychotics, benzodiazepines, opioids, and sedative-hypnotics, among other psychoactive medications, have been linked to an increased risk of falls in older adults. Furthermore, medications that affect blood pressure and blood sugar levels can have side effects that increase the risk of falls in older people. Medication use is a modifiable risk factor for falls, and older adults are especially vulnerable because of physiological changes associated with ageing.